The Alpine scandal : [large type] : an Emma Lord mystery - Daheim, Mary (Daheim, Mary. Emma Lord mystery., 2007)
Life in the peaceful town of Alpine is usually anything but. Now, the staff at The Alpine Advocate have received a suspicious obituary - mailed by the subject himself. Emma Lord and Vida Runkel try to track down the author, only to find him bludgeoned to death.